Khorij Davlatlar Armiyalarida Personification Organizational and Managerial Outsourcing Tizimidag Experimental and Unifying Analysis - Beknazarov Asqar; Ilbaev Shukhrat (European Science Publishing, 2023)
Currently, globallashuv jaraenida olib borillaetgan dzhangovar dzhangovar shurlar shursatmokdaki, shahring dzhangovar and professional tayergarliga bilan bir ryadda, ularning modern kurol-aslakh and boshkina harbiy anjomlar bilan provide security, shuningdekinjironti front in orate kasligan President of the Republic of Tajikistan Emomali Rahmon took part in the award ceremony of the President of the Republic of Tajikistan Emomali Rahmon.
Keywords: tizimi outsourcing, shipbuilding services, cross-border business, organizational partnership services, shokhshinlar on the front of organizational support, personnel of the organization, NATO logistics.